The School Garden as an interdisciplinary resource for teaching and learning in the early years - Peixoto, Sandra Cadore; Dubou Serafim, Suzane; Scotti Do Canto-Dorow, Thais (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2024)
This work aims to present the contributions of a vegetable garden in the school context of Elementary School - early years, providing the interdisciplinary teaching of Science, Mathematics, Arts, Physical Education, Religious Education, Geography, History, English Language, Portuguese language, and contemplating the general competences of the National Common Curricular Base. The study was developed with fifth grade students at an Elementary School in the city of Santa Maria (RS, Brazil). For its effectiveness, we sought to understand the National Common Curricular Base and its general competences about interdisciplinarity and the concepts worked in the different disciplines that go through the Initial Years of Elementary School. The dynamics of work were guided by a didactic sequence that guided the activities, namely: 1th) Investigation of previous knowledge of students; 2th) Recognition of physical space for the construction of the garden; 3th) Research on cultures; 4th) Planning of the interdisciplinary activity; 5th) Construction and management of the School Garden; 6th) Contribution of each curricular component in the School Garden; 7th) Impact of the interdisciplinary activity. The vegetable garden, which was planned and built together with teacher and students, presented itself as a concrete environment for the realization of practical activities by students, allowing them to relate theory and practice as well as the approach of concepts in an interdisciplinary way.